الأبعاد الجمالية للنزعة التجريدية في العمارة المعاصرة - عبدالله، الاء عبدالحميد محمد (جامعة بابل, 2021)
عني البحث الحالي بدراسة (الأبعاد الجمالية للنزعة التجريدية في العمارة المعاصرة)، احتوى البحث على أربعة فصول خصص الفصل الأول لبيان مشكلة البحث وأهميته والحاجة إليه، وتحدد مشكلة البحث. في الإجابة عن التساؤلات الآتية: ما هي المعالجات الجمالية التي اتخذتها النزعة التشكيلية التجريدية في العمارة المعاصرة؟ هل هناك اختلاف وتقارب في المعالجات الجمالية النزعة التجريدية في العمارة والفن؟ الأبعاد الجمالية للنزعة التجريدية في العمارة المعاصرة؟. كما تضمن الفصل هدف البحث وهو: تعرف الأبعاد الجمالية للنزعة التجريدية في العمارة المعاصرة وتخاذ أوسكار نيماز نموذج. وقد اقتصرت حدود البحث على الفترة الزمنية (1970-2003)، أما مكانيا تمثلت بالنماذج المعمارية المنجزة على أرض الواقع والمنفذة في البرازيل. أما الفصل الثاني: فقد تضمن الإطار النظري وقد احتوى مبحثين: عني المبحث الأول، بدراسة الأبعاد الجمالية فلسفيا والعلاقة بين الفن والعمارة وفكرتها الفلسفية التجريدية. من خلال استعراض رئي هيغل والفكر التجريدي فيما تناول المبحث الثاني التجريد في العمارة المعاصرة. أما الفصل الثالث: فقد اشتمل على إجراءات البحث المتضمنة: مجتمع البحث، عينة البحث، منهج البحث وأداة البحث والوسائل الإحصائية المستخدمة وتحليل العينة والبالغة (4) أنموذجا. أما الفصل الرابع فقد احتوى على النتائج والاستنتاجات علاوة على التوصيات، وقد توصلت الباحثة إلى نتائج أساسية نذكر منها:- 1- ظهرت الأبعاد الجمالية للنزعة التجريدية في العمارة المعاصرة فن عمارة الحداثة عبر اعتماد الاختزال الشكلي واللوني. 2- حقق اللعب الحر بالشكل والخامة والتنفيذ في تقنية الواجهات المعمارية بعدا جماليا في تشكل واجهات عمارة الحداثة كما في نماذج العينة. 3- غرائبية الفكرة التصميمية والنمط المتخيل في عرض التشكل المعماري اكسب عمارة المعاصرة بعدا جماليا." The current research concerned me with a study (the aesthetic dimensions of abstractionism in contemporary architecture). The research contains four chapters. The first chapter is devoted to explaining the research problem, its importance and the need for it, and defining the research problem. In answering the following questions: What are the aesthetic treatments taken by the abstract plasticist trend in contemporary architecture? Is there a difference and convergence in the aesthetic treatments of abstractionism in architecture and art? The aesthetic dimensions of the abstract tendency in contemporary architecture?. The chapter also included the aim of the research, which is: Know the aesthetic dimensions of abstractionism in contemporary architecture and take Oscar Niemas as a model. The research limits were limited to the time period (1970-2003), as for spatially the architectural models completed on the ground and implemented in Brazil. As for the second chapter: it included the theoretical framework and it contained two topics: The first topic was concerned with the study of the aesthetic dimensions in philosophy and the relationship between art and architecture and its philosophical abstract idea. Through a review of Hegel's vision and abstract thought, the second topic deals with abstraction in contemporary architecture. As for the third chapter: it includes the research procedures that include: The research community, the research sample, the research methodology, the research tool, the statistical means used and the sample analysis (4) as a model. As for the fourth chapter, it contained findings and conclusions in addition to recommendations. The researcher reached basic conclusions, including:- 1- The aesthetic dimensions of the abstract tendency appeared in contemporary architecture, the art of modern architecture through the adoption of formal and chromatic reduction. 2- Free play of form, material and execution in the technique of architectural façades achieved an aesthetic dimension in the formation of facades of modernity architecture as in the specimen models. 3- The exoticism of the design idea and the imagined pattern in the presentation of the architectural conformation has gained contemporary architecture an aesthetic dimension."
Keywords: الفنون التشكيلية -- العمارة المعاصرة -- المعالجات الفنية